2021
DOI: 10.18632/aging.203133
|View full text |Cite
|
Sign up to set email alerts
|

Association of growth hormone receptor gene variant with longevity in men is due to amelioration of increased mortality risk from hypertension

Abstract: The single nucleotide polymorphism (SNP) rs4130113 of the growth hormone receptor gene (GHR) is associated with longevity. Here we explored whether longevity-associated genotypes protect against mortality in all individuals, or only in individuals with aging-related diseases. Rs4130113 genotypes were tested for association with mortality in 3,557 elderly American men of Japanese ancestry. At baseline (1991-1993), 1,000 had diabetes, 730 had coronary heart disease (CHD), 1,901 had hypertension, 485 had cancer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…[97] and CYP3A5 [98] have been shown in schizophrenia. Recent studies showed that SLC6A9 [99], FKBP1B [100], S100A12 [101], SLC6A19 [102], TXN (thioredoxin) [103], TLR9 [104], HP (haptoglobin) [105], ARG1 [106], PINK1 [107], B2M [108], C5AR1 [109], MYADM (myeloid associated differentiation marker) [110], CBS (cystathionine beta-synthase) [111], GPX1 [112], SIAH2 [113], PRDX2 [114], RDH8 [115], CYP11B2 [116], RARRES2 [117], NOX1 [118], IL33 [119], OTC (ornithine transcarbamylase) [120], CYP1A1 [121], NFATC4 [122], TSLP (thymic stromal lymphopoietin) [123], WNT4 [124], MGP (matrix Gla protein) [125], FGFBP1 [126], GHR (growth hormone receptor) [127], ERBB3 [128], GFAP (glial fibrillary acidic protein) [129], CCDC40 [130], CACNB2 [131], CD34 [132], NOTCH3 [133], TERT (telomerase reverse transcriptase) [134], GNB3 [135], TP73 [136], RYR2 [137], ENPEP (glutamyl aminopeptidase) [138], SCN7A [139], WNK4 [140], SFRP5 [141], GDF15 [142], CAV1 [143], KCNA5 [144], FOXC1 [145], ASIC1 [146], VASH2 [147], CXCL8 [148], PAPPA2…”
Section: Discussionmentioning
confidence: 99%
“…[97] and CYP3A5 [98] have been shown in schizophrenia. Recent studies showed that SLC6A9 [99], FKBP1B [100], S100A12 [101], SLC6A19 [102], TXN (thioredoxin) [103], TLR9 [104], HP (haptoglobin) [105], ARG1 [106], PINK1 [107], B2M [108], C5AR1 [109], MYADM (myeloid associated differentiation marker) [110], CBS (cystathionine beta-synthase) [111], GPX1 [112], SIAH2 [113], PRDX2 [114], RDH8 [115], CYP11B2 [116], RARRES2 [117], NOX1 [118], IL33 [119], OTC (ornithine transcarbamylase) [120], CYP1A1 [121], NFATC4 [122], TSLP (thymic stromal lymphopoietin) [123], WNT4 [124], MGP (matrix Gla protein) [125], FGFBP1 [126], GHR (growth hormone receptor) [127], ERBB3 [128], GFAP (glial fibrillary acidic protein) [129], CCDC40 [130], CACNB2 [131], CD34 [132], NOTCH3 [133], TERT (telomerase reverse transcriptase) [134], GNB3 [135], TP73 [136], RYR2 [137], ENPEP (glutamyl aminopeptidase) [138], SCN7A [139], WNK4 [140], SFRP5 [141], GDF15 [142], CAV1 [143], KCNA5 [144], FOXC1 [145], ASIC1 [146], VASH2 [147], CXCL8 [148], PAPPA2…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle and genetic factors contribute to each of these conditions. We found that the increased risk of death in patients having one or more of such aging-related conditions was ameliorated by longevity-associated genotypes of the genes FOXO3 [ 9 ], mitogen-activated protein kinase kinase kinase 5 gene ( MAP3K5 ) [ 10 ], growth hormone receptor gene ( GHR ) [ 11 ], and phosphatidylinositol 3-kinase regulatory subunit 1 gene ( PIK3R1 ) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%